Inhibitor-GCPII Interaction: Selective and Robust System for Targeting Cancer Cells with Structurally Diverse Nanoparticles - Neburkova, Jitka; Sedlak, Frantisek; Zackova Suchanova, Jirina; Kostka, Libor; Sacha, Pavel; Subr, Vladimir; Etrych, Tomas; Simon, Petr; Barinkova, Jitka; Krystufek, Robin; Spanielova, Hana; Forstova, Jitka; et al. (Molecular pharmaceutics, 2018)
Glutamate carboxypeptidase II (GCPII) is a membrane protease overexpressed by prostate cancer cells and detected in the neovasculature of most solid tumors. Targeting GCPII with inhibitor-bearing nanoparticles can enable recognition, imaging, and delivery of treatments to cancer cells. Compared to methods based on antibodies and other large biomolecules, inhibitor-mediated targeting benefits from the low molecular weight of the inhibitor molecules, which are typically stable, easy-to-handle, and able to bind the enzyme with very high affinity. Although GCPII is established as a molecular target, comparing previously reported results is difficult due to the different methodological approaches used. In this work, we investigate the robustness and limitations of GCPII targeting with a diverse range of inhibitor-bearing nanoparticles (various structures, sizes, bionanointerfaces, conjugation chemistry, and surface densities of attached inhibitors). Polymer-coated nanodiamonds, virus-like particles based on bacteriophage Qβ and mouse polyomavirus, and polymeric poly(HPMA) nanoparticles with inhibitors attached by different means were synthesized and characterized. We evaluated their ability to bind GCPII and interact with cancer cells using surface plasmon resonance, inhibition assay, flow cytometry, and confocal microscopy. Regardless of the diversity of the investigated nanosystems, they all strongly interact with GCPII (most with low picomolar Ki values) and effectively target GCPII-expressing cells. The robustness of this approach was limited only by the quality of the nanoparticle bionanointerface, which must be properly designed by adding a sufficient density of hydrophilic protective polymers. We conclude that the targeting of cancer cells overexpressing GCPII is a viable approach transferable to a broad diversity of nanosystems.
Keywords: farmaceutická chemie; Hydrophobic and Hydrophilic Interactions; click chemie; cell; PSMA; Recombinant Proteins; inhibitor; virus-like particle; protinádorové látky; Neoplasms; ligandy; Cell Line, Tumor; antigeny povrchové; Click Chemistry; nanodiamond; hydrofobní a hydrofilní interakce; glutamátkarboxypeptidasa II; Ligands; Glutamate Carboxypeptidase II; Enzyme Inhibitors; Chemistry, Pharmaceutical; multivalent binding; polymer; rekombinantní proteiny; click chemistry; nonspecific interaction; lidé; Thiazolidines; GCPII; Humans; nanokonjugáty; Antigens, Surface; targeting; nádory; Nanoconjugates; nádorové buněčné linie; inhibitory enzymů; Antineoplastic Agents; thiazolidiny